Africa Agriculture Trade Monitor 2025 - Odjo, Sunday; Traoré, Fousseini; Zaki, Chahir (AKADEMIYA2063, 2025)
The 2025 Africa Agriculture Trade Monitor (AATM) investigates critical topics related to Africa’s trade in agricultural products. As in previous editions of the report, we developed a database that corrects discrepancies in official trade flow values, as reported by importing and exporting countries; this database serves as the basis for analyzing Africa’s international, domestic, and regional trade. Following the 2024 report’s examination of the nexus between climate change and the environment, this year’s report focuses on food security and its linkage with global and intra-African trade.